CPT11 with P-glycoprotein/CYP 3A4 dual-function inhibitor by self-nanoemulsifying nanoemulsion combined with gastroretentive technology to enhance the oral bioavailability and therapeutic efficacy against pancreatic adenocarcinomas - Ling-Chun Chen; Wei-Jie Cheng; Shyr-Yi Lin; Ming-Tse Hung; Ming-Thau Sheu; Hong-Liang Lin; Chien-Ming Hsieh (Taylor & Francis Group, 2021)
Therapeutic efficacies of orally administrated hydrophobic chemodrugs are decreased by poor water solubilities and reduced oral bioavailabilities by P-glycoprotein (P-gp) and CYP450. In this study, CPT11 alone or combined with dual-function inhibitors (baicalein (BA) silymarin (SM), glycyrrhizic acid (GA), and glycyrrhetinic acid (GLA)) of P-gp and CYP450 loaded in a lecithin-based self-nanoemulsifying nanoemulsion preconcentrate (LBSNENP) to improve the solubility and inhibit the elimination by P-gp and CYP450. Results revealed that the LBSNENP composed of Capryol 90, lecithin/Tween 80/Cremophor EL, and propylene glycol at a weight ratio of 18:58:24 (designated PC90C10P0) was optimally selected. Encapsulating CPT11 with PEO-7000K in PC90C10P10/30 further enhanced the resultant hydrogel to be gastro-retainable and to release CPT11 in a sustained manner. Pharmacokinetic study of CPT11-loaded PC90C10P0 administered orally revealed an absolute bioavailability (FAB, vs. intravenous CPT11) of 7.8 ± 1.01% and a relative bioavailability (FRB1, vs. oral solution of CPT11) of 70.7 ± 8.6% with a longer half-life (T1/2) and mean residence time (MRT). Among the dual-function inhibitors, SM was shown to be the most influential in increasing the oral bioavailability of CPT11. SM also increased the plasma concentration of the SN-38 active metabolite, which formed from the enhanced plasma concentration of CPT11. It is concluded that treatment with CPT11 loaded in PC90C10P0 with or without solubilization with SM could expose tumors to higher plasma concentrations of both CPT11 and SN-38 leading to enhancement of tumor growth inhibition with no signs of adverse effects.